TICRR Overexpression Enhances Disease Aggressiveness and Immune Infiltration of Cutaneous Melanoma - Chen C; Zou Y; Zheng X; Hu T; Ni J; Kan D; Yin Z; Ye L; Liu B (Dove Medical Press, 2024)
Cheng Chen, Yong Zou, Xiangbing Zheng, Taotao Hu, Jie Ni, Daohong Kan, Zongyin Yin, Lingxiao Ye, Bing Liu Department of Burn and Plastic Surgery, The Second People's Hospital of Yibin (West China Yibin Hospital, Sichuan University), Yibin, Sichuan, People's Republic of ChinaCorrespondence: Bing Liu, Email 4444093330@qq.comObjective: To investigate the role of the TopBP1 interacting checkpoint and replication regulator (TICRR) in cutaneous melanoma (CM) as a prognostic biomarker and therapeutic target.Methods: TICRR expression in tumour samples was explored using the TCGA and the GTEx database. The Kaplan-Meier survival curve, nomogram model and risk score curve were established to evaluate the prognostic role of TICRR in CM. Tissue samples of CM patients were obtained to validate the TICRR expression further. Several experiments in vitro were conducted to investigate the effect of TICRR upon CM aggressiveness and to explore underlying mechanisms.Results: TICRR was overexpressed in CM tissue and was correlated with poor prognosis of CM patients. The knockdown of TICRR decreased the proliferation, migration, and invasion of CM cells, whereas overexpression produced the opposite effect. Furthermore, TICRR suppression substantially attenuated the activation of PI3K/AKT/mTOR signalling, while the PI3K/AKT inhibitor LY294002 could partially reverse the aggressiveness-enhancing effect induced by TICRR overexpression. It was further confirmed that TICRR was closely related to immune cell infiltration activities by using immune infiltration and immunofluorescence analysis.Conclusion: TICRR overexpression may enhance CM aggressiveness by activating the PI3K/Akt/mTOR pathway and promoting immune infiltration. TICRR was verified as a potential prognostic biomarker and therapeutic target for CM.Keywords: cutaneous melanoma, TICRR, immune infiltration, invasion, prognosis